Reducing emotional reasoning: An experimental manipulation in individuals with fear of spiders - Lommen, M; Engelhard, I; van den Hout, MA; Arntz, A (2013)
Emotional reasoning involves the tendency to use subjective responses to make erroneous inferences about situations (e.g., "If I feel anxious, there must be danger") and has been implicated in various anxiety disorders. The aim of this study of individuals with fear of spiders was to test whether computerised experimental training, compared to control training, would decrease emotional reasoning, reduce fear-related danger beliefs, and increase approach behaviour towards a fear-relevant stimulus. Effects were assessed shortly after the experimental manipulation and one day later. Results showed that the manipulation significantly decreased emotional reasoning in the experimental condition, not in the control condition, and resulted in lower danger estimates of a spider, which was maintained up to one day later. No differences in approach behaviour towards the spider were found. Reducing emotional reasoning may ultimately help patients with anxiety disorders attend more to objective situational information to correct erroneous danger beliefs. © 2013 Taylor and Francis.